Electric stimulation of the vagus nerve reduced mouse neuroinflammation induced by lipopolysaccharide. Issue 1 (December 2016) - Meneses, G.; Bautista, M.; Florentino, A.; Díaz, G.; Acero, G.; Besedovsky, H.; Meneses, D.; Fleury, A.; Del Rey, A.; Gevorkian, G.; Fragoso, G.; Sciutto, E.
Abstract Background Neuroinflammation (NI) is a key feature in the pathogenesis and progression of infectious and non-infectious neuropathologies, and its amelioration usually improves the patient outcome. Peripheral inflammation may promote NI through microglia and astrocytes activation, an increased expression of inflammatory mediators and vascular permeability that may lead to neurodegeneration. Several anti-inflammatory strategies have been proposed to control peripheral inflammation. Among them, electrical stimulation of the vagus nerve (VNS) recently emerged as an alternative to effectively attenuate peripheral inflammation in a variety of pathological conditions with few side effects. Considering that NI underlies several neurologic pathologies we explored herein the possibility that electrically VNS can also exert anti-inflammatory effects in the brain. Methods NI was experimentally induced by intraperitoneal injection of bacterial lipopolysaccharide (LPS) in C57BL/6 male mice; VNS with constant voltage (5 Hz, 0.75 mA, 2 ms) was applied for 30 s, 48 or 72 h after lipopolysaccharide injection. Twenty four hours later, pro-inflammatory cytokines (IL-1β, IL-6, TNFα) levels were measured by ELISA in brain and spleen extracts and total brain cells were isolated and microglia and macrophage proliferation and activation was assessed by flow cytometry. The level of ionized calcium binding adaptor molecule (Iba-1) and glial fibrillary acidic protein (GFAP) were estimated in whole brain extracts and in histologic slides by Western blot and immunohistochemistry, respectively. Results VNS significantly reduced the central levels of pro-inflammatory cytokines and the percentage of microglia (CD11b/CD45low ) and macrophages (CD11b/CD45high ), 24 h after the electrical stimulus in LPS stimulated mice. A significantly reduced level of Iba-1 expression was also observed in whole brain extracts and in the hippocampus, suggesting a reduction in activated microglia. Conclusions VNS is a feasible therapeutic tool to attenuate the NI reaction. Considering that NI accompanies different neuropathologies VNS is a relevant alternative to modulate NI, of particular interest for chronic neurological diseases.